War in world history : - Morillo, Stephen (McGraw-Hill, 2009)
Contents: The dawn of global warfare, 1500-1750; The European transformation: Western Europe, 1500-1720; Cannon and cavalry: Eurasian expansion, 1500-1700; Conquests and contacts: Europeans abroad, 1500-1700; East Asian transformations: Japan and China, 1500-1750...